Empowering vision: the impact of nursing-led educational program on patients with dry eye syndrome - Emad Abd El Gawad Ali Rabie; Jehan Y. ElRazkey; Heba Abdelmowla Ahmed (BMC, 2024)
Abstract Background Dry eye syndrome (DES) is a widespread ocular condition affecting the general population. It is a complex disorder affecting the eye surface, characterized by a tear film imbalance and ocular symptoms such as eye ache, burning, irritation, dryness, blurred vision, and foreign body sensation. DES can reduce visual acuity, increase the risk of ocular infection, and significantly impact daily activities and quality of life. Aim Determine the impact of nursing-led educational program on the management of DES and patients' health outcomes including the intensity of DES symptoms and their influence on visual-related functions. Methods The study was conducted with a quasi-experimental design. Sixty adult patients diagnosed with DES were selected using a convenience sampling method. Two tools were employed for the collection of data. Tool I: Precipitating factors of DES structured interview schedule. Tool II: Ocular surface disease index (OSDI) to assess ocular irritation symptoms associated with DES and their effect on functions related to vision. Results A statistically significant decrease in the mean scores of OSDI in the study group two weeks after the implementation of the educational program regarding the ocular symptoms, functions associated with vision, environmental triggers, and overall score of OSDI. Conclusion Implementing an educational program for DES is effective in relieving symptoms, boosting patients' understanding of managing symptoms effectively, and maintaining eye health. Therefore, patients must be instructed on dry eye early detection and management to enhance health-related outcomes and self-care practices. Registration ClinicalTrials.gov: NCT06288945.